Temporal and Spatial Variations of Geodia cydonium (Jameson) (Porifera, Demospongiae) in the Mediterranean Confined Environments. - Mercurio, M.; Pierri, C.; Cardone, F.; Corriero, G. (Diversity, 2021)
Confinedmarine environments are particularly susceptible to climate change and anthropic pressures. Indeed, the long-term monitoring of benthic assemblages in these environments allows us to understand the direction of changes over time. The demosponge Geodia cydonium is a suitable study case, since it is widely represented in many Mediterranean environments, while being a long-living and important habitat-forming species. Here, we report the results of a descriptive study on temporal and spatial variations of this demosponge in three semi-enclosed environments along the Italian coast: Marsala Lagoon, Porto Cesareo Bay, and Mar Piccolo of Taranto. At Marsala and Porto Cesareo, the study compares the present data with those reported by the literature at the end of the 1990s. Caused by the modification of its preferential habitats, the data indicated the loss and a remarkable regression of this species at Porto Cesareo and Marsala, respectively. In addition, we hypothesized that the increase in severe weather phenomena in the small Bay of Porto Cesareo recorded during the last 20 years may have had a marked impact on water mass, thus affecting the sponge assemblages. At Taranto, despite a remarkable environmental degradation, G. cydonium has appeared stable and persistent in the last 45 years, thus representing one of the richest and most well-preserved populations in the Mediterranean Sea.